ANALISIS PEMASARAN TOMAT DI PD. INDUK KRAMAT JATI JAKARTA TIMUR - Anisah Anisah; Rini Setyowati; Sumihar ML. Tobing (Fakultas Pertanian Universitas Borobudur, 2021)
Tomato is one of the vegetables sold in the market, until now there are stillconstraints experienced by farmers tomatoes, ranging from the implementation of cultivationtechniques, pest and disease problems, to the marketing problems tomato short length ofmarketing channels tomatoes in any marketing agencies to to final consumers greatly affectthe price and marketing margin, for that tomato marketing research on the channel,agencies, marketing functions and margin analysis and marketing efisinesi tomatoes in PD.Induk Kramat Jati.The sampling method in this research is done randomly (simple randomsampling), where each member of the population of wholesalers and retailers in PD. IndukKramat Jati, The results of this study indicate 1. Marketing channels tomatoes fromproducers to consumers through PD. Induk Kramat Jati Jakarta Timur, namely farmers,traders collectors, wholesalers, retailers, consumers. 2. Institutions PD. Induk Kramat Jatimarketing contained in are wholesalers and retailers, marketing functions by each marketinginstitutions, namely exchange function, physical function, and function facilities. 3. Theamount of marketing margin spread unevenly distributed among the institutions involvedmarketing. The marketing margin tomatoes through PD. Kramat Jati Jakarta Timur, fromwholesalers to retailers, 614.5 or 24% on wholesalers, and 1,850 or 44% of retailers. 4. Itcan be seen that a very efficient marketing agencies and obtain the highest margin retailersin PD. Induk Kramat Jati East Jakarta.Keyword : Tomato, Marketing, Channel, Margin, Efisinesi